Pelaksanaan Perlindungan Terhadap Pekerja Anak Pada Usaha Asongan di Pasar Senggol Tabanan - Ni Luh Putu Yosi Pratiwi; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Preferensi Hukum, 2022)
Legal protection for children carried out in the Sengol market is based on the presence of children who work to meet the economic needs of the family which is quite difficult or because of other factors. A legal protection is the right for everyone, including children who have done work due to certain factors. However, at present the protection of child labor does not receive effective attention. Based on these problems, the purposes of this study are to reveal the implementation of legal protection for child labor in the hawker business in the Senggol Tabanan market and the inhibiting factors for the implementation of the legal protection for child labor in the hawker business in the Senggol Tabanan market. This research method is an empirical legal research with a case and legislation approach. Data collection techniques were carried out by observation and library techniques. The data sources used are primary and secondary legal sources which are then analyzed qualitatively and then the data is presented descriptively and systematically. The findings reveal that the legal protection intended for child labor in the Senggol Tabanan market is not effective in its implementation due to economic factors that are the reason the child has to work, as well as weak coordination and poor cooperation between related parties such as entrepreneurs, people parents, society, government, as well as internal factors that hinder the legal protection of child labor originating from child labor itself and external factors originating from structural, substance, and cultural factors.